Influence Of Lifestyle, Product Quality And Brand Image On Purchase Decisions With Health Awareness As Moderating Variables(Case Study Of Healthy Food Products Quaker Oat) - Irma yunita; Selfiani (Enrichment : Journal of Management, 2022)
The purpose of this study was to find out how important the level of public health awareness is to purchasing healthy food decisions by paying attention to lifestyle, product quality and brand image. This research method uses the Sem PlS 3.0 method with primary data in 2022 in the Banten community using a cluster sample of 100 respondents. The research results obtained are that there is a significant relationship between lifestyle and purchasing decisions for Quaker oat products and there is no significant relationship between product quality brand image and lifestyle on purchasing decisions partially. And simultaneously there is no finding of lifestyle, product quality and brand on purchasing decisions. There is no simultaneous ability of the health awareness variable to moderate the relationship between lifestyle, product quality and brand image on purchasing decisions